Regulation of the specific release of arachidonic acid by cytosolic phospholipase A 2 - Leslie, Christina C (Prostaglandins, leukotrienes and essential fatty acids, 2004)
Cytosolic phospholipase A 2 alpha (cPLA 2 α) is the only PLA 2 that exhibits specificity for sn-2 arachidonic acid consistent with its primary role in mediating the agonist-induced release of arachidonic acid for eicosanoid production. It is subject to complex mechanisms of regulation that ensure that levels of free arachidonic acid are tightly controlled. The calcium-induced translocation of cPLA 2 α from the cytosol to membrane regulates its interaction with phospholipid substrate. cPLA 2 α is additionally regulated by phosphorylation on sites in the catalytic domain. Because of its central position as the upstream regulatory enzyme for initiating production of several classes of bioactive lipid mediators (leukotrienes, prostaglandins and platelet-activating factor), it is a potentially important pharmacological target for the control of inflammatory diseases.